Molecular insights into onset of autoimmunity in SARS‐CoV‐2 infected patients. Issue 4 (27th October 2022) - Laxminarayana, Dama
Abstract : Molecular mechanisms involved in the induction of transient or sustained autoimmunity after SARS‐CoV‐2 infection. Highlights: Host immune‐mediated upregulation of RNA editing APOBEC3G/F and ADAR1 genes leads to the viral genome and host transcriptome editing during SARS‐CoV‐2 infections and paves the way for the generation of autoantigens. Such autoantigens will be presented as foreign by the host immune system to generate autoantibodies followed by induction of auto immunogenicity and the onset of transient or sustained autoimmune diseases as an aftermath of SARS‐CoV‐2 infections. The preventive measures and strategies are postulated to combat future SARS‐CoV‐2 infections and their aftermaths and to minimize and/or preclude SARS‐CoV‐2 mediated ill effects like autoimmune diseases. Abstract: Some of the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infected patients are facing long‐term devastating effects like induction of autoimmune diseases. Here, I discuss molecular mechanisms and risk factors involved in the induction of autoimmune diseases after SARS‐CoV‐2 infections. Transcript editing genes were upregulated during SARS‐CoV‐2 infections, which might have edited host gene transcripts and paved the way for autoantigens generation and presented as nonself to generate autoantibodies followed by auto immunogenicity after SARS‐CoV‐2 infections. Therefore, some SARS‐CoV‐2 patients acquire autoimmunity. The transient and/or innocuous autoimmune response in some SARS‐CoV‐2 infected patients may be due to a lack of repeated production of autoantibodies to host autoantigens and/or viral antigens, which are needed to boost autoimmune response. In the future, SARS‐CoV‐2 mediated autoimmune disease onset will be a challenging task. Therefore, possible preventive measures and strategies to minimize and/or preclude such SARS‐CoV‐2 mediated autoimmune diseases have been presented in this commentary.